Disequilibrium metamorphism of stressed lithosphere - Jamtveit, B.; Austrheim, H.; Putnis, Andrew (Elvevier, 2016)
© 2015 Elsevier B.V. Most changes in mineralogy, density, and rheology of the Earth's lithosphere take place by metamorphism, whereby rocks evolve through interactions between minerals and fluids. These changes are coupled with geodynamic processes and have first order effects on the global geochemical cycles of a large number of elements. In the presence of fluids, metamorphic reactions are fast compared to tectonically induced changes in pressure and temperature. Hence, rocks evolve through near-equilibrium states during fluid-producing metamorphism. However, much of the Earth's lower crust, and a significant fraction of the upper mantle do not contain free fluids. These parts of the lithosphere exist in a metastable state and are mechanically strong. When subject to changing temperature and pressure conditions at plate boundaries or elsewhere, these rocks do not react until exposed to externally derived fluids. Metamorphism of such rocks consumes fluids, and takes place far from equilibrium through a complex coupling between fluid migration, chemical reactions, and deformation processes. This disequilibrium metamorphism is characterized by fast reaction rates, dissipation of large amounts of energy as heat and work, and the generation of a range of emergent pore structures and fracture patterns that often control transport properties and thus further reaction progress. Fluid-consuming metamorphism leads to mechanical weakening due to grain size reduction, the formation of sheet silicates, and local heat production. Strain localization in the lower crust and upper mantle is therefore likely to be controlled by the availability of fluids. Fault-controlled migration of meteoric fluids from the brittle crust to the underlying ductile region in areas of compressive stress may provide a spatial and temporal link between localized strain and seismic activity in the upper crust and shear zone controlled deformation below. In a similar way, channelized fluid migration from areas undergoing prograde metamorphism in the lower plate of a subduction zone, may control the distribution of retrograde metamorphism and strain localization in the lower parts of the upper plate.